Challenges Faced by Modern Accounting as a Scientific Discipline : Four Plane Reflections - Karmańska, Anna (Olsztyn Economic Journal, 2014)
The following text presents the author's four plane reflections in relation to modern accounting as a scientific discipline. This science is becoming increasingly significant in the world at present, which is due to the fact that: (1) the accounting science (scientific discipline) is an applied science, i.e. the one that considerably enriches the accounting practice, important not only for the company which deals with accounting, (2) its research spectrum is presently extraordinarily comprehensive as it focuses on many aspects, including the social and behavioural ones, which are important for accounting. Bearing in mind that accounting in real terms in the context of the worldwide standardisation trend in the author's opinion is one of the most original systems and the one which demands exceptional professionalism from among all the information systems related to human activity, the author shares her reflections with reader on the tasks of the scientific discipline dealing with this kind of accounting in a methodical and scientific way. The planes of deliberations have been determined by: (1) unlimited data processing revolution, (2) the imperative of opposition to the traditional perception of accounting, (3) commercialisation of scientific research results, (4) ethics in scientific research.